Impact of Prenatal Stress on Amygdala Anatomy in Young Adulthood: Timing and Location Matter - Mareckova, Klara; Marecek, Radek; Andryskova, Lenka; Brazdil, Milan; Nikolova, Yuliya S (Biological psychiatry. Cognitive neuroscience and neuroimaging, 2022)
BACKGROUND: Exposure to maternal stress in utero has long-term implications for the developing brain and has been linked with a higher risk of depression. The amygdala, which develops during the early embryonic stage and is critical for emotion processing, might be particularly sensitive. METHODS: Using data from a neuroimaging follow-up of the European Longitudinal Study of Pregnancy and Childhood prenatal birth cohort (n = 129, 47% men, 23-24 years old), we studied the impact of prenatal stress during the first and second halves of pregnancy on the volume of the amygdala and its nuclei in young adult offspring. We further evaluated the relationship between amygdala anatomy and offspring depressive symptomatology. Amygdala nuclei were parcellated using FreeSurfer's automated segmentation pipeline. Depressive symptoms were measured via self-report using the Beck Depression Inventory. RESULTS: Exposure to stress during the first half of pregnancy was associated with smaller accessory basal (Cohen's f2 = 0.27, false discovery rate [FDR]-corrected p [pFDR] = .03) and cortical (Cohen's f2 = 0.29, pFDR = .03) nuclei volumes. This effect remained significant after correcting for sex, stress during the second half of pregnancy, maternal age at birth, birth weight, maternal education, and offspring's age at magnetic resonance imaging. These two nuclei showed a quadratic relationship with Beck Depression Inventory scores in young adulthood, where both smaller and larger volumes were associated with more depressive symptoms (accessory basal nucleus: adj. R2 = 0.05, pFDR = .015; cortical nucleus: adj. R2 = 0.04, pFDR = .015). CONCLUSIONS: We conclude that exposure to stress during the first half of pregnancy might have long-term implications for amygdala anatomy, which may in turn predict the experience of depressive symptoms in young adulthood.
Keywords: Magnetic Resonance Imaging; novorozenec; Infant, Newborn; magnetická rezonanční tomografie; Pregnancy; Humans; Longitudinal Studies; zpožděný efekt prenatální expozice; dítě; Child; Female; mladý dospělý; dospělí; lidé; Prenatal stress; amygdala; Adult; Amygdala nuclei; ženské pohlaví; longitudinální studie; Male; Amygdala; Magnetic resonance imaging; těhotenství; Young Adult; Amygdala volume; Depression; Prenatal Exposure Delayed Effects; mužské pohlaví; deprese